SYSTEM FOR REAL-TIME MONITORING OF TEMPERATURE, AIR HUMIDITY AND ATMOSPHERIC PRESSURE: SYSTEM FOR REAL-TIME MONITORING OF TEMPERATURE, AIR HUMIDITY AND ATMOSPHERIC PRESSURE - Kordov, Krasimir; Vichev, Stanislav (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In the present article, we present a system for monitoring the quality of air by measuring the temperature, air humidity and atmosphere pressure. The system uses Arduino microcontroller and BME280 for measuring and the obtained data is stored in database. The web based application provides real-time graphical representation of the data or the data for fixed period of time.